Aktual'nye aspekty izucenija morfologiceskich pokazatelej pedagogiceskogo kontrolja lyžnikov-dvoeborcev(obzor literatury) - Zebzeev V. V. (Vestnik sportivnoj nauki; Sports science bulletin, 2019)
In the article presents a review of modern literature on the morphological features of the body of skiers-combinators. There are known relationships between the morphological features of the body structure and the indicators characterizing the functional state and physical performance of athletes. Here described the methods of evaluation of morphological parameters of athletes at different levels of human body organization. The expediency of inclusion in the program of pedagogical control of skiers-combinators morphological indicators that have a significant impact on the effectiveness of competitive activity.